Professional Heroku programming: an architect's guide - Kemp, Chris; Gyger, Brad (Wrox programmer to programmer, 2013)
A complete guide to building and deploying web apps with Heroku A cloud application platform, Heroku is currently the only approved platform for creating apps within Facebook, and its number of users is growing at rapid pace. However, there are very few books on the market that offer professional-level coverage of this platform, until now. The author duo begins with an introduction to the Heroku platform and its associated core concepts and then goes on to explain how writing for this platform differs from that of traditional development systems. Example applications, additional resources, and advice for your next steps round out this resource, making it a thorough, indispensable guide. Features information not found anywhere else, as both authors work for Heroku Explains the inner workings of Heroku with special emphasis placed on building web and mobile applications Introduces GIT-based development workflow and the process model within the Heroku platform Details coding, building, deploying, and scaling effectively using the Heroku tool base Providing you with fully functional code and downloadable code examples, Professional Heroku Programming is your complete guide to mastering this platform.